2009
DOI: 10.1386/macp.5.3.161_1
|View full text |Cite
|
Sign up to set email alerts
|

Digital militainment by design: producing and playing SOCOM: U.S. Navy SEALs

Abstract: This article examines the nexus of global digital capitalism and US militarism in two popular war games: SOCOM I: Navy SEALs (SOCOM I) and SOCOM II: U.S. Navy SEALs (SOCOM II). SOCOM supports digital capitalism's economic interests and the US military's promotional goals in four related contexts. In its production context, SOCOM is 'glocalized digital militainment' that was synergistically co-produced by Sony Corporation (a media corporation, based in Tokyo, Japan), Zipper Interactive (a US game design firm ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 17 publications
1
3
0
1
Order By: Relevance
“…At the same time, they primarily described Bwar^as a spectacle rather than a cause of violence and destruction, highlighting the use of weaponry, the ability for players to step into the boots of a soldier, and other, very specific, aspects of Brealism.^As such, elements of representational realism were not stressed more prominently than others, meaning that elements of subjective, experiential, behavioral, and narrative realism were deemed equally relevant in marketing strategies, which corroborates Payne's (2012), and Halter's (2006) and Mirrlees' (2009) analysis. Aspects of representational realism on the other hand were perhaps taken for granted, as most gamers have already come to expect a high-quality audiovisual representation.…”
Section: Conceptualization Of Conflict/war In Promotional Game Descrisupporting
confidence: 53%
See 3 more Smart Citations
“…At the same time, they primarily described Bwar^as a spectacle rather than a cause of violence and destruction, highlighting the use of weaponry, the ability for players to step into the boots of a soldier, and other, very specific, aspects of Brealism.^As such, elements of representational realism were not stressed more prominently than others, meaning that elements of subjective, experiential, behavioral, and narrative realism were deemed equally relevant in marketing strategies, which corroborates Payne's (2012), and Halter's (2006) and Mirrlees' (2009) analysis. Aspects of representational realism on the other hand were perhaps taken for granted, as most gamers have already come to expect a high-quality audiovisual representation.…”
Section: Conceptualization Of Conflict/war In Promotional Game Descrisupporting
confidence: 53%
“…In relation to the predominance of large-scale confrontations between the great military powers, this has important ideological implications, as it potentially reinforces a misconception of the nature of contemporary warfare, and perceptions of a continued relevance of large standing armies and extended military expenditures, at a time when this is not necessarily the case. Following Stahl's discussion on the militarization of cultural space through interactive Bmilitainment^ (Mirrlees 2009;Stahl 2006;see above), it could even normalize the inevitability of future mobilizations for war, even though here, Festl et al (2013) have shown that it is too straightforward to assume that players would directly adopt such a position. Further research into how players think about the nature of Bwar^itself, however, is certainly required.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Останнім часом спостерігається зростання наукового інтересу до того, як масова культура і розважальні медіа репрезентують воєнні конфлікти з використанням пропаганди [4][5][6]. Зокрема, дедалі більшу увагу науковці приділяють відеоіграм: вони окреслили їхню роль у гарантуванні міжнародної безпеки, виявили, чим відеоігри відрізняються від інших медіа, а також дослідили потенціал відеоігор як джерела пропаганди [7][8][9][10][11][12].…”
Section: аналіз попередніх дослідженьunclassified